Assessing Charge Contribution from Thermally Treated Ni Foam as Current Collectors for Li-Ion Batteries. Issue 8 (1st January 2016) - Geaney, Hugh; McNulty, David; O'Connell, John; Holmes, Justin D.; O'Dwyer, Colm
Abstract : In this report we have investigated the use of Ni foam substrates as anode current collectors for Li-ion batteries. As the majority of reports in the literature focus on hydrothermal formation of materials on Ni foam followed by a high temperature anneal/oxidation step, we probed the fundamental electrochemical responses of as received Ni foam substrates and those subjected to heating at 100°C, 300°C and 450°C. Through cyclic voltammetry and galvanostatic testing, it is shown that the as received and 100°C annealed Ni foam show negligible electrochemical activity. However, Ni foams heated to higher temperature showed substantial electrochemical contributions which may lead to inflated capacities and incorrect interpretations of CV responses for samples subjected to high temperature anneals. XRD, XPS and SEM analyses clearly illustrate that the formation of electrochemically active NiO nanoparticles on the surface of the foam is responsible for this behavior. To further investigate the contribution of the oxidized Ni foam to the overall electrochemical response, we formed Co3 O4 nanoflowers directly on Ni foam at 450°C and showed that the resulting electrochemical response was dominated by NiO after the first 10 charge/discharge cycles. This report highlights the importance of assessing current collector activity for active materials grown on transition metal foam current collectors for Li-ion applications.